The Antimicrobial Applications of Nanoparticles in Veterinary Medicine: A Comprehensive Review - Mariana Paiva Rodrigues; Priscila Natália Pinto; Raul Roque de Souza Dias; Gabriela Lago Biscoto; Lauranne Alves Salvato; Ruben Dario Sinisterra Millán; Ricardo Mathias Orlando; Kelly Moura Keller (MDPI AG, 2023)
Nanoparticles (NPs) are nanoscaled particles sized from 1-100 nm, which can be composed of inorganic or organic compounds. NPs have distinctive morphology, size, structure, and surface features, which give them specific properties. These particular attributes make them interesting for biological and medical applications. Due to these characteristics, researchers are studying the possible aptness of numerous nanoparticles in veterinary medicine, such as the capacity to act as a drug delivery system. The use of these NPs as a possible bactericidal or bacteriostatic medication has been studied against different bacteria, especially multiresistant strains and the ones that cause mastitis disease. The antibiofilm property of these nanostructures has also already been proved. The antiviral activity has also been shown for some important viral animal diseases; the antifungal activity had been demonstrated against both pathogenic and mycotoxigenic species. Therefore, this review aimed to elucidate the main clinical and preventive veterinary applications of inorganic and organic nanoparticles.